2020
DOI: 10.1088/1755-1315/445/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of water quality and identification of pollutants flowing into river musa using principal component analysis

Abstract: Available evidence shows that rivers in any water shed area acts as a carrier of various pollutants and affect water quality for various purposes. The main aim of this study was to assess and identify pollutants flowing into River Musa in Bida for irrigaton purpose. Canadian Council Water Quality index (CCWQI) and Principal Component Analysis (PCA) were used. Water quality data were collected at different five stations along the river in 2018 during rainy and dry seasons. Ten water quality parameters (temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Thus, the surface water in the province is affected by many sources such as domestic wastewater, wastewater from industrial and agricultural activities, salinity and rainwater runoff leading to suspended matter. The study of [35,36] also revealed agricultural activities, erosion, domestic and industrial discharges are fundamental causes of water pollution. Discriminant analysis (DA) was applied to determine the level of discriminant functions (DFs) and the most important parameters affecting the change of water quality between dry season, seasonal change and rainy season as shown in Table 4.…”
Section: Correlation Among Surface Water Parametersmentioning
confidence: 99%
“…Thus, the surface water in the province is affected by many sources such as domestic wastewater, wastewater from industrial and agricultural activities, salinity and rainwater runoff leading to suspended matter. The study of [35,36] also revealed agricultural activities, erosion, domestic and industrial discharges are fundamental causes of water pollution. Discriminant analysis (DA) was applied to determine the level of discriminant functions (DFs) and the most important parameters affecting the change of water quality between dry season, seasonal change and rainy season as shown in Table 4.…”
Section: Correlation Among Surface Water Parametersmentioning
confidence: 99%